Cardiorespiratory Fitness is Associated with Glycated Hemoglobin and Triglyceride Levels in Severely Obese Men: A Retrospective Clinical Data Analysis - Wilms, Britta; Keppler, Rahel; Ernst, Barbara; Schmid, Sebastian M.; Thurnheer, Martin; Schultes, Bernd (Experimental and Clinical Endocrinology & Diabetes, 2020)
Background Even subjects with severe obesity show a wide range of metabolic health states, with some showing marked alterations in glucose and lipid metabolism whereas others do not. In severely obese women, we could recently show that the degree of cardiorespiratory fitness is, independently of body mass and age, associated with several markers of glucose and lipid metabolism.Aims In our retrospective study on a clinical data set, we questioned whether such an association also exists in severely obese men.Methods Cardiorespiratory fitness, i. e. workload (Wpeak) and oxygen uptake (V̇O2,peak) at peak exercise, was assessed by a bicycle spiroergometry in 133 severely obese men (all BMI>35 kg m−2). The following metabolic blood markers were also measured: Fasting serum glucose, insulin, triglycerides (TG), total, low-, high-density cholesterol (Chol, LDL, HDL), uric acid, and whole blood glycated hemoglobin (HbA1c). The Chol/HDL ratio and Homeostatic Model Assessment of Insulin Resistance (HOMA-IR) were also calculated.Results Multiple stepwise linear regression models including age, body mass, and smoking status as independent variables revealed that Wpeak and V̇O2,peak, explained 4.5 to 10.7% of variance in HbA1c and TG (all beta<− 0.22; all p<0.02). Including fat free mass instead of body mass in respective models revealed that both Wpeak and V̇O2,peak were predictors of HbA1c and TG (all beta<− 0.265; all p<0.013), respectively, while Wpeak also accounted for variance in glucose and Chol (both beta<− 0.259; both p<0.023).Conclusions Similar to previous observations in women, our data indicate that cardiorespiratory fitness assessed by bicycle ergospirometry test is associated with glucose and lipid metabolism in severely obese men. The strength of the found associations suggest a mild to moderate influence of cardiorespiratory fitness on metabolic health in severe obesity.
Keywords: physical fitness; obesity; glucose metabolism; lipids; spiroergometry